Positive Development Based on the Teaching of Personal and Social Responsibility: An Intervention Program With Institutionalized Youngsters - Martins, Paulo; Gonzalez, António-José; de Lima, Margarida Pedroso; Faleiro, João; Preto, Luís (Frontiers in Psychology, 2022)
From the standpoint of the school settings, sport participation constitutes a key strategy concerning the manifestation of positive behaviors that result from the development of personal and social responsibility. Based on the TPSR model, the goal of this study was to evaluate the effects of an intervention geared toward teaching life skills through sport to youngsters who had been committed. The participants were evaluated before and after the intervention. After the initial evaluation, they were randomly assigned to the experimental and control groups. The experimental group took part in the community football program, while the control group attended physical education classes not based on the TPSR model. The experimental model consisted of 3 weekly sessions over the course of 6 weeks, which totaled 18 sessions. This investigation supplied empirical evidence concerning the potential of community sport programs in the teaching and development of life skills deemed necessary for an adequate reintegration of such at-risk youngsters. The model was shown to be valid both in stimulating changes of attitudes and in promoting the adherence to socially positive behaviors. The effectiveness of the model, as well as its unique approach, make its application attractive to both the youngsters and the professionals. This program facilitates the training of youngsters to act, in the sense of promoting both their autonomy and the acquisition of a system of ethics and moral values within a culture of responsibility for how decisions affect the individual and the community. Finally, this intervention generated empirical support in favor of the argument that sport constitutes a unique opportunity within the educational process to establish values, beliefs, attitudes, and practical habits pertaining relationships and cooperation that generate social responsibility in individuals.